2018
DOI: 10.1155/2018/1235097
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Immune Process-Associated Genes in RAW264.7 Macrophage Cells in Response toBurkholderia pseudomalleiInfection

Abstract: Melioidosis is a severe and fatal tropical zoonosis, which is triggered by Burkholderia pseudomallei. To better understand the host's response to infection of B. pseudomallei, an RNA-Seq technology was used to confirm differentially expressed genes (DEGs) in RAW264.7 cells infected with B. pseudomallei. In total, 4668 DEGs were identified across three time points (4, 8, and 11 hours after infection). Short Time-Series Expression Miner (STEM) analysis revealed the temporal gene expression profiles and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Increasing evidence supports that NFKBIA -mediated inflammation is linked to susceptibility to infectious and inflammatory diseases [ 24–26 ]. A report demonstrated an up-regulation of NFKBIA expression in mouse macrophages in response to B. pseudomallei infection [ 27 ] and our data confirmed that increased NFKBIA expression is associated with fatality in melioidosis patients.…”
Section: Discussionsupporting
confidence: 89%
“…Increasing evidence supports that NFKBIA -mediated inflammation is linked to susceptibility to infectious and inflammatory diseases [ 24–26 ]. A report demonstrated an up-regulation of NFKBIA expression in mouse macrophages in response to B. pseudomallei infection [ 27 ] and our data confirmed that increased NFKBIA expression is associated with fatality in melioidosis patients.…”
Section: Discussionsupporting
confidence: 89%
“…The same samples were used for single-end 50 bp (SE50) small RNA sequencing using an Illumina HiSeq 2500 platform by Gene Denovo Biotechnology Co. (Guangzhou, China). The differentially expressed (DE) mRNAs were selected with |log2(fold change)| ≥ 1 and FDR ≤ 0.05 as we described previously (Peng et al, 2018). The expression levels of miRNAs were normalized based on the read counts to tags per million counts and |log2(fold change)| ≥ 1 and p ≤ 0.05 were the cutoffs to determine DE miRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Given that RAW264.7 cells have been widely used for modeling B. pseudomallei in vitro 16 18 , in this study we aimed to establish the B. pseudomallei HNBP001 infection model of RAW264.7 cells ( Bp ) and utilize this model to investigate the host-cell responses. For this purpose, we performed high-resolution liquid chromatography-tandem MS (LC–MS/MS) in the Bp group and negative control (NC) group 19 .…”
Section: Introductionmentioning
confidence: 99%